Religious Instruction for Soldiers in the First English Civil War, 1642–1646 - Taipale, Antti. author. (orcid)0009-0008-5606-9601 Link aut Link
IX, 284 p. 1 illus.
Keywords: This monograph examines religion in the First English Civil War (1642–1646) as a tool for war both in instructing soldiers and portraying the enemy. It argues that thus far, the remarkable differences between the teaching of Parliamentarian and Royalist ministers to their respective armies have gone largely unnoticed. Relying on the methodologies of intellectual history combined with a comparative approach, it offers a new interpretation of soldiers’ religious radicalism and highlights differences between the armies’ spiritual edification. Hence, it contributes significantly to the history of the Wars of the Three Kingdoms (1639–1653) and to the study of political radicalisation leading up to the regicide of Charles I. Moreover, it offers a detailed study of the ways in which religion was used as a tool for war in the early modern period. The role of religion has often been at the centre of historiography of the Wars of the Three Kingdoms (1639-1653). This prominence has culminated in the stereotypical character of a godly Puritan soldier, especially in relation to the New Model Army. However, while there have been debates about the role and importance of religion for the conduct and success of the armies, the theme of soldiers’ religious instruction as a tool of advice and indoctrination has received less attention. The main aim of this book is thus to rectify this lack in the historiographical mainstream and to set out a new significant interpretation of the religious character of the Civil War. Antti Taipale is a Visiting Researcher at the University of Helsinki, in Finland. His research focuses on the intellectual and cultural history of the early modern period, particularly seventeenth-century England.